2009
DOI: 10.1111/j.1365-2567.2009.03143.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell toll‐like receptor (TLR) expression differs from that of B cells, and plasma cell TLR triggering enhances immunoglobulin production

Abstract: Summary Toll‐like receptors (TLRs) are key receptors of the innate immune system and show cell subset‐specific expression. We investigated the messenger RNA (mRNA) expression of TLR genes in human haematopoietic stem cells (HSC), in naïve B cells, in memory B cells, in plasma cells from palatine tonsils and in plasma cells from peripheral blood. HSC and plasma cells showed unrestricted expression of TLR1–TLR9, in contrast to B cells which lacked TLR3, TLR4 and TLR8 but expressed mRNA of all other TLRs. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
101
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 22 publications
7
101
0
Order By: Relevance
“…While naive and memory B cells have been reported to be negative for TLR5 expression (69,70), flagellin was recently found to promote the generation and/or survival of short-lived plasma cells, and data suggest that TLR5 expression on these cells contributes to this effect (42). In addition, activated B cells were found to upregulate the expression of TLR5 (42).…”
Section: Discussionmentioning
confidence: 90%
“…While naive and memory B cells have been reported to be negative for TLR5 expression (69,70), flagellin was recently found to promote the generation and/or survival of short-lived plasma cells, and data suggest that TLR5 expression on these cells contributes to this effect (42). In addition, activated B cells were found to upregulate the expression of TLR5 (42).…”
Section: Discussionmentioning
confidence: 90%
“…MPL is a Toll-like receptor 4 (TLR4) agonist derived from Salmonella enterica serovar Minnesota, and it induces strong Th1 and IL-12 responses (16). Tonsillar memory and naïve B cells do not express TLR4; however, PC do (14). Their expansion seen here may be due in part to the TLR4-containing adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…125 In contrast, endosomal TLRs such as TLR7, a receptor for single-stranded RNA, and TLR9, a receptor for unmethylated CpGmotifs containing DNA, are highly expressed in B cells. [124][125][126] The activation of TLR7 and TLR9 by RNA and DNA initiates signaling via recruitment of the adaptor molecule MyD88 and the sequential activation of NF-κB, MAPKs, AP-1 and IRF-7, resulting in B cell proliferation and immunoglobulin production. [124][125][126] However, many vaccine adjuvants contain ligands for surface TLR, including monophosphoryl lipid A, suggesting that TLR activation on other important cells such as DC, tissue structural cells or T cells can promote robust B cell responses.…”
Section: Tlrmentioning
confidence: 99%
“…[124][125][126] The activation of TLR7 and TLR9 by RNA and DNA initiates signaling via recruitment of the adaptor molecule MyD88 and the sequential activation of NF-κB, MAPKs, AP-1 and IRF-7, resulting in B cell proliferation and immunoglobulin production. [124][125][126] However, many vaccine adjuvants contain ligands for surface TLR, including monophosphoryl lipid A, suggesting that TLR activation on other important cells such as DC, tissue structural cells or T cells can promote robust B cell responses. 124,125 Interestingly, a recent study showed that B cells respond rapidly during sepsis and play an important role in a rapid innate immune response via an interferon activation pathway downstream of TLR activation.…”
Section: Tlrmentioning
confidence: 99%